Experimental and numerical analysis of RC beams strengthened with ECC and stainless steel strips. Issue 5 (7th March 2023) - Hamoda, Ahmed; Emara, Mohamed; Abdelazeem, Fathi; Ahmed, Mizan
Abstract : Strengthening of reinforced concrete (RC) structures may be required for several reasons and flexural strengthening of normal concrete (NC) beams is widely carried out using laminated fibres. However, the incompatibility of the concrete cover can lead to fibre debonding or concrete cover dislocation. These are some of the critical setbacks in common practice and the cost of fibre can be high. A novel flexural strengthening technique for NC beams is thus proposed: durable strips of stainless steel plate (SSP) bonded over a engineered cementitious composite (ECC), which is in complete contact with the flexural reinforcement of a slave beam through shear connectors. The flexural behaviour of NC beams strengthened with ECC and SSP strips was investigated experimentally and numerically. Three variables were investigated: the thickness of the SSP, the ECC layer with or without deformed steel bars and three different strengthening techniques. The experimental results showed that hybrid ECC–SSP strengthening improved the ultimate capacity of the NC beams by as much as 156%. A three-dimensional finite-element model (FEM) was developed and validated using the experimental results. The FEM accurately predicted the experimentally observed flexural behaviour of the NC beams with hybrid ECC–SSP strengthening. An analytical model to predict the ultimate load of NC beams with hybrid ECC–SSP strengthening was also developed.